Role of Communication in Fostering Development and Societal Stability: A Pathway to Sustainable Growth in Nigeria. - Chile, Martha Fashimaiter Chile (African Journal of Stability and Development (AJSD), 2025)
Communication is a fundamental driver of national development and societal stability, serving as a tool for governance, social cohesion, and economic progress. This study examined the role of communication in fostering development and stability in Nigeria, highlighting its significance in shaping public discourse, promoting inclusive governance, and addressing socio-political challenges. Despite its critical role, communication in Nigeria faces numerous obstacles, including media bias, misinformation, digital exclusion, and political interference. These have hindered its effectiveness in fostering sustainable growth. Grounded in Social Stability Theory and Development Communication Theory, this study explored how effective communication strategies contributed to national development by fostering civic engagement, strengthening institutions, and promoting peacebuilding initiatives. A qualitative research approach was adopted, relying on secondary data sourced from scholarly articles, policy documents, and case studies. Thematic analysis was employed to identify key trends, insights, and challenges related to communication’s role in national stability and development. Findings revealed that well-structured communication initiatives, such as government-led campaigns, Nollywood productions, and grassroots media interventions, can significantly influence public awareness, governance, and social cohesion. However, challenges such as political control of media, the digital divide, and the spread of misinformation remain pressing concerns. The study recommended strengthening media independence, improving digital access, and fostering participatory communication strategies to enhance the role of communication in Nigeria’s sustainable development. Future research should explore the evolving impact of digital media on political stability and the effectiveness of indigenous communication methods in governance.